Software Quality. Software and Systems Quality in Distributed and Mobile Environments : 7th International Conference, SWQD 2015, Vienna, Austria, January 20-23, 2015, Proceedings - Winkler, Dietmar; Biffl, Stefan; Bergsmann, Johannes (Lecture Notes in Business Information Processing,, 2015)
This book constitutes the refereed proceedings of the scientific track of the 7th Software Quality Days Conference, SWQD 2015, held in Vienna, Austria, in January 2015. The SWQD conference offers a range of comprehensive and valuable information by presenting new ideas from the latest research papers, keynote speeches by renowned academics and industry leaders, professional lectures, exhibits, and tutorials. The four scientific full papers accepted for SWQD were each peer reviewed by three or more reviewers and selected out of 13 high-quality submissions. Further, four short papers were also presented and are included in this book. The papers are organized into topical sections on risk management and inspection, change impact analysis and systems testing, and software and systems architectures.